Integrating ICT Solutions for Sustainable Agriculture: Addressing Food Security in the Face of Climate Change - Simwinga, Gideon Mulenga; Shemi, Alice P.S; Moyo, Paul (Zambia ICT Journal, 2025)
Climate change poses an escalating threat to global food security, necessitating innovative approaches to agricultural practices. This paper explores how Information and Communication Technology (ICT) can revolutionize agriculture, emphasizing precision agriculture, mobile technologies, and data analytics. The study examines socio-economic and infrastructural barriers to ICT adoption, offering a detailed framework for scaling ICT solutions in rural and resource-constrained areas. By leveraging a comprehensive analysis of case studies and emerging technologies, the findings highlight the transformative potential of ICT in enhancing resource efficiency, increasing yields, and mitigating climate change impacts. This research contributes to bridging theory and practice, supporting sustainable agricultural development and global food security.